Adiabatic Mixed‐Field Orientation of Ground‐State‐Selected Carbonyl Sulfide Molecules. Issue 22 (26th September 2016) - Kienitz, Jens S.; Trippel, Sebastian; Mullins, Terry; Długołęcki, Karol; González‐Férez, Rosario; Küpper, Jochen
Abstract: A strong adiabatic mixed‐field orientation ( N up / N tot =0.882) of carbonyl sulfide (OCS) molecules in their absolute ground state is experimentally demonstrated. OCS is oriented in a combination of nonresonant laser and static electric fields inside a two‐plate velocity map imaging spectrometer. The transition from nonadiabatic to adiabatic orientation for the rotational ground state is studied by varying the applied laser intensity and static electric field. Above static electric field strengths of 10 kV cm −1 and laser intensities of 10 11 W cm −2 the observed degree of orientation reaches a plateau. These results are in good agreement with computational solutions of the time‐dependent Schrödinger equation. Abstract : Molecular orientation : Carbonyl sulfide (OCS) molecules are oriented in a combination of nonresonant laser and static electric fields inside a two‐plate velocity map imaging (VMI) spectrometer (see figure), and the transition from nonadiabatic to adiabatic orientation for the rotational ground state is studied by varying the applied laser intensity and strength of the static electric field.